A prospective, open label clinical study to evaluate the safety, efficacy and tolerability of azadvir herbal steam inhaler in asymptomatic, mildly symptomatic COVID-19 patients and health care workers posted to covid wards - Pottirayil, Ajitha; S., Shankar A.; Kannoth, Shaji; Prasad, Poorna; Jaikar, Sharath Kumar B.; Reddy, L. Manjunath (International Journal of Basic & Clinical Pharmacology, 2021)
Background: COVID-19 patients experience cytokine storm which cause pulmonary and extra-pulmonary complications even with currently available of standard of care. Additional antiviral and immune boosters are the need of hour to treat COVID-19 and to prevent post covid complications. Methods: In this study we enrolled 40 asymptomatic to mild COVID-19 patients to receive azadvir herbal steam inhaler along with standard of care. We evaluated the benefits of azadvir herbal steam inhaler by assessing RT-PCR conversion, clinical outcomes and improvement in immune markers (LDH, CRP, D-DIMER). Results: At the end of the study the immune markers improved significantly in study patients. In mild symptomatic cases IL-6 was 23.2 pg/ml on day 0 and 21.8 pg/ml on day 14. Reduction in IL-6 in mild symptomatic patients was statistically highly significant (p=0.0056). Mean IL-6 in asymptomatic patients was 22.3 pg/ml on day 0 and 21.1 pg/ml on day 14. Reduction in IL-6 in asymptomatic patients was statistically highly significant (p=0.0035). Mean D-dimer was showing decreasing trend from day 0 to day 14 in mild symptomatic patients. In asymptomatic patients D dimer was 0.8 µg/ml on day 0 and 0.6 µg/ml on day 14. D-dimer decreased significantly from day 0 to day 14 (p value =0.0013). Mean LDH values on day 0 in mild symptomatic patients was 319.4 U/l and 219.3 on day 14. The reduction in LDH values in mild symptomatic patients is statistically significant (p value <0.0122). In asymptomatic patients mean LDH values on day 0 was 237 U/l and 194 U/l on day 14. The reduction in LDH values in asymptomatic group was statistically significant. Mean CRP values in mild symptomatic patients on day 0 was 12.2 mg/l and 3.8 mg/l on day 14. There was significant reduction in CRP values in mild symptomatic group which was statistically significant (p value =0.0546). Mean CRP values in asymptomatic patients on day 0 was 4.9 mg/l and 2.8 mg/l on day 14. There was significant reduction in mean CRP in asymptomatic patients which was statistically significant (p value =0.0446). In the present study all 40 patients (100%) cleared the virus and became negative for RT PCR test within 6 days. None of the patients progressed to severe COVID-19 and none of the patients succumbed to the disease. Conclusions: Azadvir accelerated recovery of COVID-19 patients by RT-PCR conversion, early improvement in clinical symptoms and immune markers in this study. This study results clearly indicates that azadvir has antiviral, immune booster activity and has definitive role in the management of asymptomatic to mild COVID-19 patients along with standard of care (CTRI no. CTRI/2020/06/026181).